The value of lactate dehydrogenase to albumin ratio and immune inflammation biomarkers in colorectal cancer - Wu, Jiali; Wu, Ao; Wang, Songzi; Zeng, Chunxian; Wang, Ruizhi; Zhou, Juan; Wang, Dong (Frontiers in Surgery, 2023)
Abstract Background: Colorectal cancer (CRC) is one of the most prevalent gastrointestinal cancers. Evidence for the importance of inflammation and immunology in the development and progression of CRC is growing steadily. The purpose of this study was to determine the clinical importance of Lactic Dehydrogenase (LDH) to Albumin (ALB) Ratio (LAR) and immune-inflammation biomarkers (IIBs) in patients with CRC. Methods: This study enrolled 382 CRC patients. The LAR was determined as the serum LDH(U/L) to ALB(g/L) ratio. We compared the levels of LAR and IIBs in different TNM stages and tumor differentiation. The relationship between LAR and IIBs and overall survival (OS) of CRC were determined by Cox regression models. A prognostic nomogram was created using the results of the multivariate analysis and the effectiveness of the nomogram was assessed using the ROC, calibration, and decision curves. We evaluated the relationship between LAR and IIBs and clinical features of CRC. Results: The levels of LAR, SII, NLR and PLR in TNM IV stage group (LAR:5.92(5.23-8.24); SII: 1040.02(499.51-1683.54); NLR: 2.87 (2.07-5.3); PLR:187.08(125.31-276.63)) were significantly higher than those in other groups. LAR and NLR showed no significant difference in different tumor differentiation groups, while SII and PLR in undifferentiated groups(SII:543.72(372.63-1110.20); PLR: 147.06 (106.04-203.92)) were significantly higher than those in well and moderate groups (SII: 474.29(323.75-716.01); PLR: 126.28 (104.31-167.88)). LAR(HR=1.317, 95% CI=1.019-1.454), TNM stage(HR=2.895, 95% CI=1.838-4.559), age(HR=1.766, 95% CI=1.069-2.922) and lymphocytes(HR=0.663, 95% CI=0.456-0.963) were predictors of OS. IIBs, including SII, NLR, and PLR are independent of OS. The LAR-based nomogram AUCs of 1-year, 3-year and 5-year survival probabilities in the training cohort were 0.86, 0.72, and 0.71, respectively, and the AUCs of the validation cohort were 0.85, 0.71, and 0.69 respectively. The LAR-based nomogram's ROC curves and calibration curves demonstrated higher OS discriminative performance. The decision curves demonstrated greater net benefit in the survival prediction. Conclusion: Preoperative LAR is a potential prognostic marker in CRC patients, while SII, NLR, and PLR are independent of OS. LAR was associated with tumor stage in CRC patients, but not with tumor differentiation.